PERAN KEPEMILIKAN INSTITUSIONAL DALAM MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - Dwi Oktaviani (AKUNTANSI DEWANTARA, 2019)
Tax revenue in Indonesia has not reach an optimum number because the revenue target has not fulfilled yet. This condition alleged because the tax avoidance practices that done by company is still high. This phenomenan becomes background of the need to examine what factors that influence the company in practicing tax avoidance. This research aims to analyze the influence of executive character, firm size, and profitability on tax avoidance with institutional ownership as moderating variable. The population in this study is property, real estate, and construction companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The sampling technique used is purposive sampling technique and obtain 35 samples with 175 units of analysis. The data analysis tool used is panel regression using the Eviews program version 9.0. The result of this study prove that the executive character and firm size has a significant positive effect on tax avoidance, while profitability does not significantly influence on tax avoidance. Meanwhile, institusional ownership is not able to moderate the influence of executive character, firm size and profitability on tax avoidance.